3D конечно-разностная миграция поля преломленных волн - Верпаховская, А.О.; Пилипенко, В.Н.; Вудкевич, В.В. (Геофизический журнал, 2015)
Запропоновано метод 3D скінченно-різницевої міграції поля заломлених хвиль, який враховує їх проникнення у заломлювальну товщу. Наведено теоретичні основи та особливості методу тривимірної скінченно-різницевої глибинної міграції поля заломлених хвиль. Ефективність і можливості застосування запропонованого методу 3D скінченно-різницевої міграції поля заломлених хвиль продемонстровано на модельному прикладі. A method of 3D finite-difference migration of the field of refracted waves is proposed, which takes into account their penetration into refracting strata. Theoretical grounds and special features of the method of finite-difference deep migration of the field of refracted waves have been presented in the paper. Effectiveness and facilities of application of proposed method of 3D finite- difference migration of the field of refracted waves have been demonstrated on the model example.